Threats to speleological heritage from jandaíra, rn: the importance of environmental preservation - Silva, Hudson Alves da; Alves, Laís Rodrigues; Silva, Lourdes Caroline Pereira da; Ferreira, Marcela Rejane da Silva (Geosaberes; Vol 8 No 14 (2017): Jan - Apr, 2017)
Jandaíra - RN, inserted into mesoregion Agreste Potiguar and microrregion Baixa Verde, presents major areas of karst relief with an incidence of caves, which suffer continuous threats of lime and cement industry as well as disordered visits, causing depredation and pollution to speleological heritage. Considering the above, we aimed to discuss the importance of environmental preservation in areas where they occur the caves of Jandaíra, given the high potential paleontological and speleological, from the environmental studies conducted at the sector analyzed with students from Course of Degree in Geography Federal Institute of Education, Science and Technology of Rio Grande do Norte, Natal Central Campus and guides Cavernature Group of Speleology (Speleological Association, Socio-Cultural and Environmental History from the City of Jandaíra - RN). The results showed that the analyzed area suffers from the exploitation of limestone rock, existing caatinga deforestation to feed the furnaces in adjacent industries, graffiti and pollution of cave environments. This way, we conclude that there is an absence of public authorities with initiatives to minimize such impacts, as well as the deficiency in promoting scientific research reveals the existence of possible fossils in the study area.
Keywords: Cavernas; Jandaíra; Preservação ambiental; relevo cárstico